Battery

By optimizing the battery material system and meeting the specific safety factor relationship, the problem that existing batteries cannot take into account high energy density, cycle capacity retention rate and safety are solved, and higher battery performance and stability are achieved.

CN119518112APending Publication Date: 2025-02-25EVE ENERGY CO LTD

Patent Information

Application Number
CN202411701990.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing batteries cannot take into account both high energy density, cycle capacity retention and safety, especially performance requirements at high temperatures and high cycle times are difficult to meet.

Method used

By optimizing the material system of the battery, including the physical properties parameters of the positive electrode current collector, the negative electrode current collector and the separator, it is ensured that the specific safety factor relationship is met between its tensile strength, elongation, film rupture temperature, thermal shrinkage rate and closed-cell temperature, so as to improve the safety and electrochemical performance of the battery.

Benefits of technology

The capacity retention rates of the battery at 25℃ for 1000 weeks and 45℃ for 600 weeks were achieved to reach 89% and 87%, respectively, and passed 100% in the 130℃ thermal abuse test, meeting the requirements of high energy density, circulation capacity retention and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518112A_ABST
    Figure CN119518112A_ABST
Patent Text Reader

Abstract

The invention discloses a battery, and belongs to the technical field of batteries. The battery comprises a positive current collector, a negative current collector and a diaphragm, the tensile strength a1 of the positive current collector, the tensile strength a2 of the negative current collector, the elongation b1 of the positive current collector, the elongation b2 of the negative current collector, the diaphragm rupture temperature c, the diaphragm thermal shrinkage rate d and the diaphragm hole closing temperature e meet the following relational expression: N1 = (a1 + a2) * (b1 + b2) * c / d / e, wherein the N1 is the safety coefficient of the battery, and the N1 is 416 to 25600. The battery disclosed by the invention can simultaneously consider high energy density, high cycle capacity retention ratio and safety, and meets the technical requirements of customers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular, to a battery. Background Art

[0002] The current battery material system uses ordinary strength foil, a diaphragm with large thermal shrinkage and low tensile strength, and an electrolyte containing only conventional additives. This material system has the problems of failure due to thermal abuse (130℃ / 1H) and low cycle capacity retention rate. Under high voltage (>4.45V), steel shell batteries must simultaneously meet four performance indicators: high energy density, capacity retention rate ≥80% after 800 cycles at 25℃, capacity retention rate ≥80% after 600 cycles at 45℃, and 100% safety performance. The current battery cells cannot take into account the three performances at the same time, so it is necessary to improve the material system selection and other aspects to improve the high energy density of the battery, ensure qualified safety performance and qualified cycle capacity retention rate, so as to meet the market demand for the electrical performance of steel shell batteries. Summary of the invention

[0003] The main purpose of the present application is to provide a battery to solve the problem in the prior art that the battery cannot simultaneously take into account high energy density, cycle capacity retention rate and safety.

[0004] According to one aspect of the present application, a battery is provided, comprising a positive electrode current collector, a negative electrode current collector and a separator; the tensile strength of the positive electrode current collector, the tensile strength of the negative electrode current collector, the room-temperature elongation of the positive electrode current collector, the room-temperature elongation of the negative electrode current collector, the film rupture temperature of the separator, the thermal shrinkage rate of the separator and the closed-pore temperature of the separator satisfy the following relationship:

[0005] N1=(a1+a2)×(b1+b2)×c÷d÷e;

[0006] Among them, N1 is the safety factor of the battery, N1 is 416~25600;

[0007] a1 is the tensile strength of the positive electrode collector; a2 is the tensile strength of the negative electrode collector; b1 is the room temperature elongation of the positive electrode collector; b2 is the room temperature elongation of the negative electrode collector; c is the film rupture temperature of the base film; d is the thermal shrinkage rate of the base film; e is the closed pore temperature of the base film.

[0008] Furthermore, the safety factor N1 of the battery is 880-25600; optionally, it can be 1700-25600.

[0009] Furthermore, the tensile strength a1 of the positive electrode current collector is 50-80, and can be optionally 60-80.

[0010] Furthermore, the tensile strength a2 of the negative electrode current collector is 50-80, and can be optionally 60-80.

[0011] Furthermore, the room temperature elongation b1 of the positive electrode current collector is 5 to 8%; optionally 6 to 8%.

[0012] Furthermore, the room temperature elongation b2 of the negative electrode current collector is 5 to 8%; optionally 6 to 8%.

[0013] Furthermore, the membrane rupture temperature c of the diaphragm is 150-250°C; optionally 180-250°C; or optionally 200-250°C.

[0014] Furthermore, the heat shrinkage rate d of the base film is 0.5-2.0%; optionally 0.5-1.8%; or optionally 0.5-1.5%.

[0015] Furthermore, the closed-cell temperature e of the base film is 50-180°C; optionally 50-150°C; or optionally 50-120°C.

[0016] Furthermore, the temperature of the normal temperature is 15-30.

[0017] Furthermore, the positive electrode current collector is selected from at least one of an aluminum current collector, a nickel current collector, a stainless steel current collector and a carbon current collector; and may be an aluminum foil or a nickel foil.

[0018] Furthermore, the negative electrode current collector is selected from at least one of a copper current collector, a nickel current collector, a stainless steel current collector and a carbon current collector; and may be copper foil or nickel foil.

[0019] Furthermore, the diaphragm includes a base film and a base film coating layer attached to a surface of the base film.

[0020] Furthermore, the base film is selected from at least one of a polypropylene film, a polyethylene film, an aramid film and a cellulose film.

[0021] Further, the base film coating includes a single-sided coating or a double-sided coating.

[0022] Furthermore, the material of the base film coating includes ceramics and / or polymers.

[0023] Further, the ceramic includes at least one of magnesium hydroxide, magnesium oxide, aluminum oxide and boehmite.

[0024] Furthermore, the polymer is polyvinylidene fluoride or polymethyl methacrylate.

[0025] Furthermore, the diaphragm includes, from the first surface to the opposite second surface, in sequence: a ceramic coating, a base film and a ceramic coating; or a ceramic coating, a base film and a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a ceramic coating, and a polymer adhesive layer.

[0026] Furthermore, the active material of the positive electrode coating attached to the surface of the positive electrode current collector includes at least one of lithium iron phosphate, lithium cobalt oxide, and ternary materials.

[0027] Furthermore, the active material of the negative electrode coating attached to the surface of the negative electrode current collector includes at least one of graphite, silicon carbon, and silicon oxygen.

[0028] Furthermore, the electrolyte in the battery is selected from at least one of a liquid electrolyte, a gel electrolyte, and a solid electrolyte.

[0029] By applying the technical solution of the present application, a battery is provided, the capacity of which is about 5% higher than that of the soft-pack battery of the same type on the market; the capacity retention rate of the battery can reach 89% after 1000 cycles at 25°C (1.3C charging / 1C discharging), and the capacity retention rate can reach 87% after 600 cycles at 45°C (1.3C charging / 1C discharging), and the thermal abuse test (130°C / 1H) is 100% passed; the battery of the present application can take into account high energy density, cycle capacity retention rate and safety at the same time, and meet the technical requirements of similar customers. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0031] Figure 1 is a schematic diagram of the battery structure of an embodiment of the present application;

[0032] Figure 2 It is a schematic diagram of the structure of the positive electrode sheet in the battery of the embodiment of the present application;

[0033] Figure 3 It is a 25°C cycle performance curve of the battery in Example 2 and Comparative Example 4 of the present application;

[0034] Figure 4 It is a 45°C cycle performance curve of the battery in Example 2 and Comparative Example 4 of the present application.

[0035] Reference numerals:

[0036] 1-positive electrode sheet, 11-positive electrode current collector, 12-positive electrode coating;

[0037] 2-negative electrode sheet, 21-negative electrode current collector, 22-negative electrode coating;

[0038] 3-diaphragm, 31-base membrane, 32-base membrane coating;

[0039] 4-Electrolyte. DETAILED DESCRIPTION

[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0041] In order to solve the problem that the battery in the prior art cannot take into account high energy density, cycle capacity retention rate and safety at the same time, the present application has developed a new battery, including a positive current collector, a negative current collector and a separator; the tensile strength of the positive current collector, the tensile strength of the negative current collector, the room temperature elongation of the positive current collector, the room temperature elongation of the negative current collector, the film breaking temperature of the base film, the thermal shrinkage rate of the base film and the closed pore temperature of the base film satisfy the following relationship:

[0042] N1=(a1+a2)×(b1+b2)×c÷d÷e;

[0043] Among them, N1 is the safety factor of the battery;

[0044] a1 is the tensile strength of the positive electrode collector; a2 is the tensile strength of the negative electrode collector; b1 is the room temperature elongation of the positive electrode collector (%); b2 is the room temperature elongation of the negative electrode collector (%); c is the rupture temperature of the base film; d is the thermal shrinkage rate of the base film (%); e is the closed pore temperature of the base film.

[0045] In the battery structure of the present application, the positive and negative current collectors are important carriers for carrying active substances, current collection and transmission, and electrochemical reactions. The diaphragm is a carrier that prevents the positive and negative electrodes from contacting and for ion transmission. The physical parameters and performance of these two materials and the reasonable matching between the two are important links in battery design, and both significantly affect the battery safety performance and electrical performance.

[0046] The battery safety performance of the present application is positively correlated with the tensile strength and elongation of the aluminum foil and copper foil; when the deformation of the electrode active material during the battery charging and discharging process exerts a force on the battery collector, the aluminum foil and copper foil with appropriate tensile strength and elongation are conducive to improving the stability of the battery structure, thereby improving the safety performance of the battery under charging and discharging conditions. The battery safety performance is also positively correlated with the membrane breaking strength of the diaphragm, and negatively correlated with the closed-cell temperature and thermal shrinkage rate of the diaphragm; for a suitable closed-cell temperature diaphragm, when the battery is overheated, the diaphragm melts under the action of high temperature to block the micropores on the diaphragm, and the resistance rises by 2-3 orders of magnitude, cutting off the current and preventing the temperature from continuing to rise; for a suitable membrane breaking temperature diaphragm, the structural stability can be maintained at high temperatures, avoiding the occurrence of internal short circuits caused by thermal shrinkage and structural damage, which is conducive to further improving the electrochemical performance of the battery; for a suitable thermal shrinkage diaphragm, the short-circuit resistance of the battery can be improved in a high temperature environment, the structural stability of the diaphragm can be maintained, and the battery safety performance can be improved. However, the best matching effect cannot be achieved if the current collector tensile strength, elongation, and diaphragm temperature are too high or too low, and the battery performance may not reach the most ideal performance; when the safety factor N1 designed in this application is small, the strength of the current collector and the diaphragm is small, and the battery collapses and shrinks under mechanical abuse and high temperature conditions, causing the positive and negative electrodes to short-circuit, affecting the battery safety performance. When the safety factor N1 is large, the battery processing and preparation process is difficult and affects the insertion and extraction of lithium ions between the positive and negative electrodes, thereby affecting the kinetic performance and electrochemical performance of the battery. Therefore, this application finds that when the current collector tensile strength, the current collector room temperature elongation, the diaphragm film rupture temperature, the diaphragm closed hole temperature, and the diaphragm thermal shrinkage rate meet the N1 relationship, they can better play a synergistic role with each other, and promote the battery to have better electrochemical performance and stability.

[0047] The above-mentioned battery designed in the present application has a capacity that is about 5% higher than the soft-pack battery of the same type on the market; the battery of the present application can maintain a capacity of 89% after 1000 cycles at 25°C (1.3C charging / 1C discharging), and a capacity retention rate of 87% after 600 cycles at 45°C (1.3C charging / 1C discharging), and has passed the thermal abuse test (130°C / 1H) 100%; it can take into account high energy density, cycle capacity retention rate and safety at the same time; it can be applied to consumer batteries, power batteries, energy storage batteries, etc.; for example, it can be used in mobile communication devices such as mobile phones.

[0048] In some embodiments, the safety factor N1 of the battery of the present application is 880-25600.

[0049] The safety factor N1 of the present application is controlled within the above range. The capacity retention rate of the battery after 1000 cycles at room temperature (1.3C charging / 1C discharging) is 85%, and the capacity retention rate of the battery after 600 cycles at a high temperature of 45°C is above 84%.

[0050] In some embodiments, the safety factor N1 of the battery is 1700-25600.

[0051] The safety factor N1 of the present application is within the above range. The capacity retention rate of the battery after 1000 cycles at room temperature (1.3C charging / 1C discharging) is 89%, and the capacity retention rate of the battery after 600 cycles at a high temperature of 45°C is about 87%.

[0052] In some embodiments, the safety factor N1 of the battery is 3000-11020.

[0053] When the safety factor of the battery of the present application is within the above range, the capacity retention rate of the battery after 1000 cycles at room temperature (1.3C charging / 1C discharging) is 88%, and the capacity retention rate of the battery after 600 cycles at a high temperature of 45°C is above 87%.

[0054] In some embodiments, the tensile strength a1 of the positive electrode current collector of the battery of the present application is 50-80, or 55-80, or 60-80.

[0055] When the present application selects a positive electrode current collector with a tensile strength within the above range, it is beneficial to improve the impact strength of the battery when the positive electrode current collector is subjected to mechanical abuse, thereby improving the battery safety factor N1.

[0056] In some embodiments, the tensile strength a2 of the negative electrode current collector is 50-80, may be 55-80, or may be 60-80.

[0057] When the present application selects a negative electrode current collector with a tensile strength within the above range, it is beneficial to improve the impact strength of the battery when the negative electrode current collector is subjected to mechanical abuse, thereby improving the battery safety factor N1.

[0058] In some embodiments, the room temperature elongation b1 of the positive electrode current collector is 5 to 8%, may be 6 to 8%, or may be 6.5 to 8%.

[0059] When the present application selects a positive electrode current collector with a room-temperature elongation within the above range, it is beneficial to improve the impact strength of the battery when the positive electrode current collector is subjected to mechanical abuse, thereby improving the battery safety factor N1.

[0060] In some embodiments, the room temperature elongation b2 of the negative electrode current collector is 5 to 8%, may be 6 to 8%, or may be 6.5 to 8%.

[0061] When the present application selects a negative electrode current collector with a room temperature elongation within the above range, when the negative electrode current collector is subjected to mechanical abuse, it is beneficial to improve the impact strength of the battery, thereby improving the battery safety factor N1.

[0062] In some embodiments, the diaphragm rupture temperature c of the battery of the present application is 150-250°C, can be 180-250°C, or can be 200-250°C.

[0063] When the present application selects a diaphragm material with a rupture temperature within the above-mentioned temperature range, the diaphragm can ensure the integrity of the diaphragm at high temperatures, will not cause diaphragm damage, and will not cause a short circuit between the positive and negative electrodes. The diaphragm material can enhance the battery's ability to resist short circuits in high temperature environments, thereby enhancing the battery's safety performance.

[0064] In some embodiments, the thermal shrinkage rate d of the separator of the battery of the present application is 0.5-2.0%, may be 0.5-1.8%, or may be 0.5-1.5%.

[0065] When the present application selects a diaphragm material with a thermal shrinkage rate within the above-mentioned temperature range, the diaphragm material can enhance the short-circuit resistance of the battery in a high-temperature environment, thereby enhancing the safety performance of the battery.

[0066] In some embodiments, the diaphragm closed-cell temperature e of the battery of the present application is 50-180°C, may be 50-150°C, or may be 50-120°C.

[0067] When the present application selects a diaphragm material with a closed-cell temperature within the above-mentioned temperature range, the lower the closed-cell temperature, the more closed cells are formed in the diaphragm after the temperature rises to a certain level, thereby isolating the positive and negative electrodes and preventing internal short circuits; the diaphragm material can enhance the battery's ability to resist short circuits in high-temperature environments, thereby enhancing the battery's safety performance.

[0068] Under the premise of satisfying the above-mentioned tensile strength, room temperature elongation, diaphragm rupture temperature, diaphragm closed pore temperature and diaphragm thermal shrinkage rate of the positive electrode current collector, the present application further screens the structures of the positive and negative electrode current collectors and diaphragms, and finds that the battery performance can be further improved.

[0069] In some embodiments, the positive electrode current collector of the battery of the present application is selected from at least one of an aluminum current collector, a nickel current collector, a stainless steel current collector, and a carbon current collector; for example, aluminum foil or nickel foil.

[0070] The positive electrode current collector material and active material selected in the present application have good bonding and good conductivity, and can improve the electrochemical performance of the battery.

[0071] In some embodiments, the negative electrode current collector is selected from at least one of a copper current collector, a nickel current collector, a stainless steel current collector, and a carbon current collector; for example, a copper foil or a nickel foil.

[0072] The negative electrode current collector material and active material selected in the present application have good bonding and good conductivity, and can improve the electrochemical performance of the battery.

[0073] In some embodiments, the copper foil selected in the present application has a grain size of 0.2-0.4 μm and has a (220) crystal plane.

[0074] The grain size range and 220 crystal plane selected in the present application are both beneficial to improving the tensile strength and elongation of the copper foil, thereby improving the mechanical properties of the battery. If the grain size continues to increase, it may lead to a decrease in tensile strength.

[0075] In some embodiments, the diaphragm includes a base membrane and a base membrane coating attached to the surface of the base membrane; wherein the base membrane is selected from at least one of a polypropylene film, a polyethylene film, an aramid film and a cellulose film; the base membrane coating includes a single-sided coating or a double-sided coating; the material of the base membrane coating includes ceramics and / or polymers; the ceramics include at least one of magnesium hydroxide, magnesium oxide, aluminum oxide and boehmite; the polymer is polyvinylidene fluoride or polymethyl methacrylate.

[0076] In some embodiments, the diaphragm includes, from the first surface to the opposite second surface, in sequence: a ceramic coating, a base film and a ceramic coating; or a ceramic coating, a base film and a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a ceramic coating, and a polymer adhesive layer.

[0077] This application uses a diaphragm with the above coating, with ceramic coating on the surface of the base membrane + water-based PVDF glue spraying, which further improves thermal stability and ensures adhesion while having high air permeability, which is conducive to ion conduction. The surface of the base membrane is cast polyethylene. When the battery is overheated, the polyethylene melts under high temperature to block the micropores on the base membrane, and can maintain structural stability at higher temperatures, avoiding thermal shrinkage and structural collapse that cause short circuits in the battery.

[0078] The above-mentioned base membrane selected in the present application, in terms of base membrane pore size, base membrane porosity, permeability, thickness, material, coating, etc., has better safety and high-temperature cycle performance in terms of electrochemical performance.

[0079] In some embodiments, the active material of the positive electrode coating attached to the surface of the positive electrode current collector selected in the present application includes at least one of lithium iron phosphate, lithium cobalt oxide, and a ternary material; the active material of the negative electrode coating attached to the surface of the negative electrode current collector includes at least one of graphite, silicon carbon, and silicon oxygen materials; the electrolyte is selected from at least one of a liquid electrolyte, a gel electrolyte, and a solid electrolyte.

[0080] The present application selects the above-mentioned active materials to form a positive electrode coating or a negative electrode coating, which has better capacity and energy density, better cycle stability and better electrochemical performance.

[0081] From a microscopic analysis, the surface density of the positive electrode collector, the wettability of the positive electrode collector, the number of pinholes of the positive electrode collector, the surface density of the negative electrode collector, the wettability of the negative electrode collector, the number of pinholes of the negative electrode collector, the porosity of the base film and the air permeability of the base film have the following relationship: N2 = (ρ1ⅹr1÷n1+ρ2ⅹr2÷n2)÷(pⅹg); wherein N2 is the battery safety factor, N2 is 0.143~4.545; it can be 0.286~4.545; it can also be 1.389~4.545.

[0082] ρ1 is the surface density of the positive electrode collector; ρ2 is the surface density of the negative electrode collector; r1 is the wettability of the positive electrode collector; r2 is the wettability of the negative electrode collector; n1 is the number of pinholes in the positive electrode collector; n2 is the number of pinholes in the negative electrode collector; p is the porosity of the base film; g is the air permeability of the base film.

[0083] For example, the units of ρ1 and ρ2 can be g / m 2 The unit of r1 and r2 can be mN / m, and the unit of n1 and n2 can be pieces / m 2 The unit of p can be %, and the unit of g can be sec / 100ml.

[0084] For example, the surface density ρ1 of the positive electrode current collector is 10 to 30 g / m 2 ; The surface density of the negative electrode collector is ρ2 10 to 30 g / m 2 ; The wetness of the positive electrode current collector r1 is 30-50 mN / m; The wetness of the negative electrode current collector r2 is 30-50 mN / m; The number of pinholes n1 of the positive electrode current collector is 2-50 / m 2 ; The number of pinholes n2 of the negative electrode current collector is 2 to 50 / m 2 ; The porosity p of the base film is 30-40%; The air permeability g of the base film is 110-210 sec / 100 ml. Furthermore, the surface density ρ1 of the positive electrode current collector is 15-30 g / m 2 ; The surface density of the negative electrode collector is ρ2 15 ~ 30g / m 2 ; The wetness of the positive electrode current collector r1 is 40-50 mN / m; The wetness of the negative electrode current collector r2 is 40-50 mN / m; The number of pinholes n1 of the positive electrode current collector is 20-50 / m 2 ; The number of pinholes n2 of the negative electrode current collector is 20 to 50 / m 2 ; The porosity p of the basement membrane is 34-40%; The air permeability g of the basement membrane is 130-210 sec / 100 ml.

[0085] For example, the number of aluminum chips in the cross section of the positive electrode current collector is 2 to 25 pieces / 10 cm. 2The smooth surface roughness is 0.02-0.38 μm, the matte surface roughness is 0.05-2 μm; the cross-section copper shavings of the negative electrode current collector are 2-25 pieces / 10 cm 2 The roughness of the smooth surface is 0.02~0.38μm, the roughness of the matte surface is 0.05~2μm; the thickness of the base film is 4~12μm.

[0086] Since the tensile strength and elongation of copper and aluminum foil are positively correlated with the surface density and wettability; the greater the wettability of copper and aluminum foil, the better the wettability with carbon materials, the stronger the adhesion of slurry, the greater the peeling force between slurry and foil, the less likely it is to expose foil and scratch, the easier it is to weld the pole ear, and it is resistant to electrolyte immersion, with lower internal resistance, suitable for fast charging and discharging; and the enhanced adhesion can improve the phenomenon of easy detachment of pole pieces and loss of electrical contact of active materials, and improve the disadvantage of increased contact resistance of batteries; and the increase of active material loading and surface density can effectively improve the energy density, wettability, cycle and rate performance and electrical performance consistency of batteries; and the appropriate wettability and surface density can improve the tensile strength and elongation, improve the mechanical properties of foil, reduce the risk of pole piece breaking during rolling, and significantly improve the thermal stability of batteries, thereby improving the safety performance of batteries. The number of pinholes in copper and aluminum foil is negatively correlated with its tensile strength. The more pinholes there are, the lower the tensile strength will be, thus reducing the safety performance of batteries. For the diaphragm, the greater the porosity and the higher the air permeability of the base film, the lower its tensile strength and puncture strength will be, which will reduce the battery safety performance. When N2 is small, the strength of the current collector and the diaphragm is relatively small. Under mechanical abuse and high temperature conditions, the structure of the battery may collapse and shrink, causing a short circuit between the positive and negative electrodes, affecting the battery safety performance; when N2 is large, the battery processing and preparation process is difficult and affects the embedding and extraction of lithium ions between the positive and negative electrodes, thereby affecting the battery's kinetic and electrochemical performance. When N2 is large, the thicker pole piece affects the embedding and extraction of lithium ions, causing lithium ions to easily precipitate on the negative electrode surface, thereby affecting the battery's kinetic performance, cycle performance and safety performance. The current collector surface density, current collector wettability, number of current collector pinholes, base film porosity, and base film permeability are within a specific range, and there is a good synergistic effect between them, which can promote the battery to have better electrochemical performance and stability.

[0087] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0088] Example 1

[0089] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode collector 11 and a positive electrode coating 12 (active material is lithium iron phosphate) attached to the surface of the aluminum foil; the tensile strength of the aluminum foil is a1, which is 50 MPa, and the elongation at room temperature b1 (25°C) is 5%; the negative electrode sheet 2 comprises a copper foil negative electrode collector 21 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the tensile strength of the copper foil is a2, which is 50 MPa, and the elongation at room temperature b2 (25°C) is 5 %; the diaphragm 3 includes a polypropylene base film 31 and a base film coating 32 attached to the surface of the base film; both sides of the polypropylene base film 31 are sequentially attached with a magnesium hydroxide ceramic material layer and a PVDF base film adhesive layer; the film breaking temperature c of the base film 31 is 150°C, the thermal shrinkage rate d of the base film 31 is 2%, and the closed-cell temperature e of the base film 31 is 180°C; the electrolyte 4 is a liquid electrolyte; the safety factor of the battery N1=(a1+a2)×(b1+b2)×c÷d÷e=416; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 As shown,

[0090] Example 2

[0091] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode current collector and a positive electrode coating 12 (active material is lithium iron phosphate) attached to the surface of the aluminum foil; the tensile strength a1 of the aluminum foil is 55 MPa, and the elongation b1 (25°C) at room temperature is 6%; the negative electrode sheet 2 comprises a copper foil negative electrode current collector 21 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the tensile strength a2 of the copper foil is 55 MPa, and the elongation b2 (25°C) at room temperature is 6%; the separator 3 comprises a polyethylene base film 31 and a base film coating 32 attached to the surface of the base film; a magnesium oxide ceramic coating is attached to one surface of the polyethylene, and a PVDF adhesive layer is attached to the other opposite surface, such as Figure 2 As shown; the film breaking temperature c of the base film 31 is 180°C, the heat shrinkage rate d of the base film 31 is 1.8%, and the closed-cell temperature e of the base film 31 is 150°C; the electrolyte 4 is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 880; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as shown Figure 1 As shown, the diaphragm structure is Figure 2 As shown, the performance test is as follows Figure 3 and Figure 4 shown.

[0092] Example 3

[0093] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode current collector 11 and a positive electrode coating 12 (active material is lithium iron phosphate) attached to the surface of the aluminum foil; the aluminum foil (model LM16-053-76, copper foil model BFR8SSU-0320F2) has a tensile strength a1 of 60 MPa and a room temperature elongation b1 (25°C) of 6.5%; the negative electrode sheet 2 comprises a copper foil negative electrode current collector 2 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the copper foil (BFR8SSU-032 0F2) has a tensile strength a2 of 60Mpa and a room temperature elongation b2 (25°C) of 6.5%; the diaphragm 3 comprises a composite base film of polyethylene and polypropylene and a base film coating 32 attached to the surface of the composite base film; both sides of the composite film are attached with a magnesium oxide ceramic coating; the rupture temperature c of the base film is 200°C, the thermal shrinkage rate d of the base film is 1.5%, and the closed-cell temperature e of the base film is 120°C; the electrolyte is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 1732; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 shown.

[0094] Example 4

[0095] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode current collector 11 and a positive electrode coating 12 attached to the surface of the aluminum foil (the active material is lithium iron phosphate); the tensile strength of the aluminum foil is a1, which is 70 MPa, and the elongation at room temperature b1 (25°C) is 7%; the negative electrode sheet 2 comprises a copper foil negative electrode current collector 21 and a negative electrode coating 22 attached to the surface of the copper foil (the active material is graphite); the tensile strength of the copper foil is a2, which is 70 MPa, and the elongation at room temperature b1 (25°C) is 7%. The rate b2 (25°C) is 7%; the diaphragm includes a polyethylene and polypropylene composite base film 31 and a base film coating 32 attached to the surface of the base film; both sides of the composite film are attached with a magnesium oxide ceramic coating; the base film has a film breaking temperature c of 220°C, a heat shrinkage rate d of 1%, and a closed-cell temperature e of 90°C; the electrolyte is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 4792; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 shown.

[0096] Example 5

[0097] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode collector 11 and a positive electrode coating 12 (active material is lithium iron phosphate) attached to the surface of the aluminum foil; the tensile strength of the aluminum foil is a1, which is 75 MPa, and the elongation at room temperature b1 (25°C) is 7.5%; the negative electrode sheet 2 comprises a copper foil negative electrode collector 21 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the tensile strength of the copper foil is a2, which is 75 MPa, and the elongation at room temperature b1 (25°C) is 7.5%. 2 (25 ℃) is 7.5%; the diaphragm 3 includes a polyethylene and polypropylene composite base film 31 and a base film coating 32 attached to the surface of the base film; both sides of the composite film are attached with a magnesium oxide ceramic coating; the base film has a film breaking temperature c of 240 ℃, a thermal shrinkage rate d of the base film of 0.7%, and a closed-cell temperature e of the base film of 70 ℃; the electrolyte is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 11020; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 shown.

[0098] Example 6

[0099] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode collector 11 and a positive electrode coating 12 (active material is lithium iron phosphate) attached to the surface of the aluminum foil; the tensile strength of the aluminum foil is a1, which is 80 MPa, and the elongation at room temperature b1 (25°C) is 8%; the negative electrode sheet 2 comprises a copper foil negative electrode collector 21 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the tensile strength of the copper foil is a2, which is 80 MPa, and the elongation at room temperature b1 (25°C) is 8%. 2 (25 ℃) is 8%; the diaphragm 3 includes a polyethylene and polypropylene composite base film 31 and a base film coating 32 attached to the surface of the base film; both sides of the composite film are attached with a magnesium oxide ceramic coating; the base film has a film breaking temperature c of 250 ℃, a thermal shrinkage rate d of the base film of 0.5%, and a closed-cell temperature e of the base film of 50 ℃; the electrolyte is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 25600; the specific structure is shown in Table 1; the performance test is shown in Table 2; the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 shown.

[0100] Example 7

[0101] A battery, comprising a positive electrode sheet 1, a negative electrode sheet 2, a separator 3 and an electrolyte 4; the positive electrode sheet 1 comprises an aluminum foil positive electrode current collector 11 and a positive electrode coating 12 (active material is lithium cobalt oxide) attached to the surface of the aluminum foil; the tensile strength of the aluminum foil is a1, which is 60 MPa, and the elongation at room temperature b1 (25°C) is 7%; the negative electrode sheet 2 comprises a copper foil negative electrode current collector 21 and a negative electrode coating 22 (active material is graphite) attached to the surface of the copper foil; the tensile strength of the copper foil is a2, which is 70 MPa, and the elongation at room temperature b1 (25°C) is 7%. The elongation rate b2 (25°C) is 8%; the diaphragm 3 includes a polyethylene and polypropylene composite base film 31 and a base film coating 32 attached to the surface of the base film; both sides of the composite film are attached with a magnesium oxide ceramic coating; the base film has a film breaking temperature c of 210°C, a thermal shrinkage rate d of the base film of 1.2%, and a closed-cell temperature e of the base film of 100°C; the electrolyte is a liquid electrolyte; the safety factor of the battery N = (a1 + a2) × (b1 + b2) × c ÷ d ÷ e = 3412.5; see Table 1 for details, the battery structure is as follows Figure 1 As shown, the diaphragm structure is Figure 2 shown.

[0102] Comparative Example 1

[0103] The difference between this comparative example 1 and the embodiment 1 is that the tensile strength, room temperature elongation, film breaking temperature, thermal shrinkage rate and pore closing temperature of the positive and negative current collectors are different; see Table 1 for details. The mechanical and electrochemical properties of the above battery were tested, and the results are shown in Table 2.

[0104] Comparative Example 2

[0105] The difference between this comparative example 3 and example 1 is that the tensile strength, room temperature elongation, film breaking temperature, thermal shrinkage rate and pore closing temperature of the positive and negative current collectors are different; see Table 1 for details. The mechanical and electrochemical properties of the above battery were tested, and the results are shown in Table 2.

[0106] Comparative Example 3

[0107] The difference between this comparative example 4 and the embodiment 1 is that the tensile strength, room temperature elongation, film breaking temperature, thermal shrinkage rate and pore closing temperature of the positive and negative current collectors are different; see Table 1 for details. The mechanical and electrochemical properties of the above battery were tested, and the results are shown in Table 2.

[0108] Comparative Example 4

[0109] Commercially available conventional battery, model 486266.

[0110] The performance of each battery was tested using the following method.

[0111] (1) Battery 130℃5℃ / min thermal abuse test method: After charging from 0.5C to 0.05C, place the battery cell in a test chamber after standing for 30 minutes. The temperature in the test chamber is raised to 130±2℃ at a rate of (5±2℃) / min. When the temperature reaches 130±2℃, keep the temperature constant for 60 minutes. After the test, take out the battery cell and visually inspect its appearance at room temperature. The test equipment is a high-temperature test oven.

[0112] (2) Drop performance test method: Place the battery in a fixture at 25±3℃, and drop it freely from a height of 1.8m onto an iron plate, for a total of 18 drops (stick sponge glue and baffles, and stick it in the fixture with double-sided quick-release adhesive) up→down→upper right→lower right→upper left→lower left, 3 cycles (corner 45±15 degrees). After the test is completed, take it back to the disassembly room for disassembly. The test equipment is a drop tester.

[0113] (3) Test method for heavy object impact: At 25±3℃, charge the battery cell from 0.5C to 0.05C, let it stand for 30 minutes, and then place the battery cell on the impact test bench; place a 15.8±0.1mm metal rod horizontally on the upper surface of the geometric center of the battery cell, and use a 9.1±0.1kg weight to hit the surface of the battery cell with the metal rod in a free fall state from a height of 610±25mm, and observe for 6 hours, and record the temperature rise data. The test equipment is a heavy object impact test bench.

[0114] (4) Test method for room temperature cycle performance: at 25°C, charge to 4.16V at 1.3C, cut off at 1C; charge to 4.28V at 1C, cut off at 0.8C; charge to 4.47V at 0.8C, cut off at 0.1C; let stand for 10 minutes; discharge to cut off voltage 3.3V at 0.5C; let stand for 10 minutes; perform the above charge and discharge cycles for the specified number of cycles (1000 cycles); among which 1 / 100 / 200 / 300 / 400 / 500 / 600 / 700 / 800 / 900 / 1000 / 1100 / 1200 cycles are tested according to the following steps: at 23±2°C, charge to 4.47V at 0.2C, cut off at 0.02C; let stand for 10 minutes; discharge to cut off voltage 2.75V at 0.2C; let stand for 10 minutes; record the capacity retention rate after the cycle is completed. The test equipment is the Xinwei battery cycle test cabinet.

[0115] (5) Test method for 45℃ cycle performance: At 45±2℃, charge to 4.16V at 1.3C, cut off at 1C; charge to 4.28V at 1C, cut off at 0.8C; charge to 4.47V at 0.8C, cut off at 0.1C; let stand for 10min; discharge to cut off voltage 3.0V at 1C; let stand for 10min; perform the above charge and discharge cycle for the specified number of cycles (600 cycles); among which 1 / 100 / 200 / 300 / 400 / 500 / 600 cycles are tested according to the following steps: At 45±2℃, charge to 4.47V at 0.2C, cut off at 0.02C; let stand for 10min; discharge to cut off voltage 2.75V at 0.2C; let stand for 10min; record the capacity retention rate after the cycle is completed. The test equipment is the Xinwei battery cycle test cabinet.

[0116] Table 1

[0117]

[0118] Table 2

[0119]

[0120]

[0121] Note: Thermal abuse, drop, and heavy object impact test pass standards: 100% no fire, no smoke, and no explosion; 25°C cycle pass standard: 1000-cycle capacity retention rate ≥ 80%; 45°C cycle pass standard: 600-cycle capacity retention rate ≥ 80%.

[0122] It can be seen from the data in Table 1 and Table 2 that the embodiments 1 to 7 listed in the present application use a positive electrode collector material with a tensile strength a1 of 50 to 80 MPa, a negative electrode collector material with a tensile strength a2 of 50 to 80 MPa, a positive electrode collector material with a room temperature elongation b1 of 5% to 8%, a negative electrode collector material with a room temperature elongation b2 of 5% to 8%, a film rupture temperature c of 150°C to 250°C, a thermal shrinkage rate d of 0.5% to 2%, and a base film material with a closed cell temperature e of 50°C to 180°C. The safety factor N1 = (a1+a2) × (b1+b2) × c÷d÷e is 416 to 25600 between the various structural factors.

[0123] The test results in Table 2 show that the battery capacity retention rate designed in this application is 31% to 39% higher than that of Comparative Example 1 at room temperature, 11% to 19% higher than that of Comparative Example 2, and 3% to 11% higher than that of Comparative Example 3; at high temperatures, it is 2% to 9% higher than that of Comparative Example 1, 5% to 12% higher than that of Comparative Example 2, and 1% to 7% higher than that of Comparative Example 3. The battery capacity designed in this application is about 5% higher than that of the same model of soft-pack batteries on the market in Comparative Example 4. Figure 3 and Figure 4As shown. The batteries of Examples 1 to 7 of the present application have a capacity retention rate of 81% to 89% for 1000 cycles at room temperature (1.3C charge / 1C discharge), a capacity retention rate of 80% to 87% for 600 cycles at 45°C (1.3C charge / 1C discharge), and 100% pass the thermal abuse test (130°C / 1H); high energy density, cycle capacity retention rate, and safety can be taken into account at the same time. Among them, the tensile strength and room temperature elongation of the positive current collector and the negative current collector materials can be kept consistent or inconsistent.

[0124] The battery safety factors N1 of Comparative Examples 1 to 3 are 40, 130, and 280000, respectively. The tensile strength of the positive current collector, the tensile strength of the negative current collector, the room temperature elongation of the positive current collector, the room temperature elongation of the negative current collector, the membrane breaking temperature of the diaphragm, the thermal shrinkage rate of the diaphragm, and the closed-pore temperature of the diaphragm are not properly selected and do not match each other. Multiple structural materials cannot achieve a good synergistic effect, resulting in a safety factor that is too large or too small; a safety factor that is too large will affect the battery's kinetic performance and electrochemical performance; a safety factor that is too small may be due to the low strength or mismatch of the current collector and the diaphragm, which may cause the battery structure to shrink easily under mechanical abuse or high temperature conditions, ultimately affecting the battery's safety performance and electrochemical performance.

[0125] For example, the current collector of Comparative Example 1 has relatively low tensile strength and elongation, and its membrane rupture temperature is too low. It is not heat-resistant, and its mechanical and heat resistance are poor. In addition, the optimal matching effect is not achieved between multiple material factors, resulting in the membrane rupture easily when the battery generates heat during charging and discharging, causing the battery to short-circuit, have poor thermal abuse resistance, and poor resistance to falling and heavy object impact, which greatly reduces the battery safety. The battery has a capacity retention rate of only 50% at room temperature, and its electrochemical performance is significantly reduced.

[0126] Although the tensile strength of the current collector in Comparative Example 2 is similar to that of the embodiment of the present application, the membrane rupture temperature is too low, and the membrane rupture phenomenon is likely to occur, resulting in a short circuit in the battery, affecting the battery safety and electrochemical performance. At the same time, the thermal shrinkage of the diaphragm is relatively high, and the short circuit resistance is poor in a high temperature environment, making the diaphragm structure unstable, affecting the battery safety. The capacity retention rate at room temperature is 70%, and the high temperature capacity retention rate is 75%, which is significantly lower than that of the present application. The above results further illustrate that the best synergistic effect can only be achieved when the current collector and the diaphragm are appropriately selected and their performances match each other.

[0127] The current collector of comparative example 3 has too high tensile strength, relatively high elongation, too high film breaking temperature, and 100% pass rate of thermal abuse test, but the thermal shrinkage is too small and the closed-cell temperature is too low, which will affect the insertion and extraction of lithium ions between the positive and negative electrodes, and thus affect the battery kinetics and electrochemical performance; although the selection of positive and negative current collectors is relatively appropriate, the drop and heavy impact performance does not reach 100% pass rate, indicating that the effects of multiple influencing factors have not reached the effect of mutual synergy to promote battery performance. The above also further illustrates that the best synergistic effect can only be achieved when the selection of current collectors and separators is appropriate and the performance matches each other.

[0128] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0129] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A battery comprising a positive electrode current collector, a negative electrode current collector and a separator; characterized in that: The tensile strength of the positive electrode current collector, the tensile strength of the negative electrode current collector, the room temperature elongation of the positive electrode current collector, the room temperature elongation of the negative electrode current collector, the film rupture temperature of the separator, the thermal shrinkage rate of the separator and the closed pore temperature of the separator satisfy the following relationship: N1=(a1+a2)×(b1+b2)×c÷d÷e; Wherein, N1 is the safety factor of the battery, and N1 is 416 to 25600; a1 is the tensile strength of the positive electrode collector; a2 is the tensile strength of the negative electrode collector; b1 is the room temperature elongation of the positive electrode collector; b2 is the room temperature elongation of the negative electrode collector; c is the film rupture temperature of the base film; d is the thermal shrinkage rate of the base film; e is the closed pore temperature of the base film.

2. The battery according to claim 1, characterized in that The safety factor N1 of the battery is 880 to 25600, preferably 1700 to 25600.

3. The battery according to claim 1 or 2, characterized in that: The tensile strength a1 of the positive electrode current collector is 50 to 80, preferably 60 to 80; And / or, the tensile strength a2 of the negative electrode current collector is 50-80, preferably 60-80.

4. The battery according to any one of claims 1 to 3, characterized in that: The room temperature elongation b1 of the positive electrode current collector is 5 to 8%, preferably 6 to 8%. And / or, the room temperature elongation b2 of the negative electrode current collector is 5 to 8%, preferably 6 to 8%.

5. The battery according to any one of claims 1 to 4, characterized in that: The membrane breaking temperature c of the diaphragm is 150-250°C; preferably 180-250°C; more preferably 200-250°C; And / or, the heat shrinkage rate d of the base film is 0.5 to 2.0%; preferably 0.5 to 1.8%; more preferably 0.5 to 1.5%; And / or, the closed cell temperature e of the base film is 50 to 180°C; preferably 50 to 150°C; more preferably 50 to 120°C; And / or, the normal temperature is 15-30°C.

6. The battery according to any one of claims 1 to 5, characterized in that: The positive electrode current collector is selected from at least one of an aluminum current collector, a nickel current collector, a stainless steel current collector and a carbon current collector; preferably an aluminum foil or a nickel foil; And / or, the negative electrode current collector is selected from at least one of a copper current collector, a nickel current collector, a stainless steel current collector and a carbon current collector; preferably copper foil or nickel foil.

7. The battery according to any one of claims 1 to 6, characterized in that: The diaphragm includes a base film and a base film coating attached to the surface of the base film; Preferably, the base film is selected from at least one of a polypropylene film, a polyethylene film, an aramid film and a cellulose film; Preferably, the base film coating comprises a single-sided coating or a double-sided coating.

8. The battery according to claim 7, characterized in that The material of the base film coating includes ceramic and / or polymer; Preferably, the ceramic comprises at least one of magnesium hydroxide, magnesium oxide, aluminum oxide and boehmite; Preferably, the polymer is polyvinylidene fluoride or polymethyl methacrylate.

9. The battery according to any one of claims 1 to 8, characterized in that: The diaphragm includes, from the first surface to the opposite second surface, in sequence: a ceramic coating, a base film and a ceramic coating; or a ceramic coating, a base film and a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a polymer adhesive layer; or a polymer adhesive layer, a ceramic coating, a base film, a ceramic coating, and a polymer adhesive layer.

10. The battery according to claim 9, characterized in that The active material of the positive electrode coating attached to the surface of the positive electrode current collector includes at least one of lithium iron phosphate, lithium cobalt oxide, and ternary materials; And / or, the active material of the negative electrode coating attached to the surface of the positive electrode current collector includes at least one of graphite, silicon carbon, and silicon oxygen; And / or, the electrolyte in the battery is selected from at least one of a liquid electrolyte, a gel electrolyte, and a solid electrolyte.

Citation Information

Patent Citations

  • Composite microporous membrane used as lithium ion battery diaphragm as well as preparation method and application thereof

    CN102122704A

  • Flexible composite ceramic membrane with low temperature closed-cell performance and good dimensional stability

    CN103066227A

  • Secondary battery and terminal

    CN113937415A

  • Composite current collector and preparation method therefor, and lithium ion battery

    WO2023151400A1

  • Coating slurry, high-temperature resistant coating film and preparation method therefor, and electrochemical device

    WO2023284619A1

Cited By

  • Non-aqueous electrolyte secondary battery

    WO2026182218A1